2004
DOI: 10.1128/jvi.78.7.3252-3261.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the Evolutionary History of Rice Yellow Mottle Virus from Genomic, Phylogenetic, and Phylogeographic Studies

Abstract: Fourteen isolates of Rice yellow mottle virus (RYMV) were selected as representative of the genetic variability of the virus in Africa from a total set of 320 isolates serologically typed or partially sequenced. The 14 isolates were fully sequenced and analyzed together with two previously reported sequences. RYMV had a genomic organization similar to that of Cocksfoot mottle sobemovirus. The average nucleotide diversity among the 16 isolates of RYMV was 7%, and the maximum diversity between any two isolates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 41 publications
3
96
0
Order By: Relevance
“…Separate comparisons for the RdRp and CP ORFs indicated nt identities >94% and >95%, respectively, amongst the 21 isolates (Table 3). These results are equivalent to those observed for the sobemovirus Rice yellow mottle virus (RYMV), for which the average nt diversity for the full genomic sequences of 16 isolates was 7%, and the maximum diversity between any two isolates was 10% (Fargette et al, 2004). Considering that some of the locations where the samples were collected are approximately 370 km apart, that samples were collected within a one-year interval ( Table 1), and that the dN/dS ratios for the RdRp and CP ORFs were 0.108 and 0.185, respectively, the genetic variability of the virus can be considered to be low.…”
Section: Sequence Comparisonssupporting
confidence: 59%
See 1 more Smart Citation
“…Separate comparisons for the RdRp and CP ORFs indicated nt identities >94% and >95%, respectively, amongst the 21 isolates (Table 3). These results are equivalent to those observed for the sobemovirus Rice yellow mottle virus (RYMV), for which the average nt diversity for the full genomic sequences of 16 isolates was 7%, and the maximum diversity between any two isolates was 10% (Fargette et al, 2004). Considering that some of the locations where the samples were collected are approximately 370 km apart, that samples were collected within a one-year interval ( Table 1), and that the dN/dS ratios for the RdRp and CP ORFs were 0.108 and 0.185, respectively, the genetic variability of the virus can be considered to be low.…”
Section: Sequence Comparisonssupporting
confidence: 59%
“…Furthermore, the number of complete sobemovirus sequences is low, and therefore it is difficult to state which region of the genome (if any) could be representative of the entire genome (Truve & Fargette, 2011). The study by Fargette et al (2004) indicates that the CP is quite variable (our data shows the same) but at the same time, phylogenetic trees based on the entire genome or the CP sequence have very similar topologies. Therefore, at least for RYMV, the CP sequence can be used to type isolates.…”
Section: Phylogenetic Analysismentioning
confidence: 71%
“…No intra-specific or inter-specific recombinant sobemoviruses have been described so far. Based on the phylogenetic analysis of 14 RYMV full-length isolates and 58 capsid protein genes sequences, it has been concluded that RYMV evolved in the absence of recombination events (Chare and Holmes, 2006;Fargette et al, 2004). Similarly, on the basis of the phylogenetic comparison of six sobemovirus genomes, including CfMV, RYMV, Lucerne transient streak virus (LTSV), Sesbania mosaic virus (SeMV), Southern cowpea mosaic virus (SCPMV), and Southern bean mosaic virus (SBMV), it was suggested that recombination is neither frequent nor significant in the sobemovirus group (Lokesh et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…1. As described before (Fargette et al, 2004), the P1 sequence displays a high diversity fairly well distributed along the nucleotide sequence.…”
mentioning
confidence: 88%
“…In addition, samples used in this study were collected in nine countries in Africa, including regions where a large proportion of the viral diversity is concentrated [i.e. eastern Tanzania (Fargette et al, 2004)]. Thus, the high number of sites positively selected is related to the genetic diversity of the P1 protein and to the sampling used, which is, itself, representative of the evolutionary history of RYMV.…”
mentioning
confidence: 99%